HUBUNGAN KECEMASAN SOSIAL DIGITAL DENGAN KEMAMPUAN ASERTIVITAS PADA SISWA SEKOLAH MENENGAH PERTAMA - Kiki Rizki Aulia (Akademi Kebidanan Harapan Bunda Bima, 2025)
The rapid development of digital technology has transformed patterns of social interaction among students at SMPN 2 Wera Bima and may influence adaptive social skills, including assertiveness. This study aimed to examine the effect of digital social anxiety on students’ assertiveness at SMPN 2 Wera Bima. A quantitative approach was employed using a quasi-experimental pretest–posttest control group design. Participants consisted of students aged 12–15 years, who were assigned to an experimental group and a control group. The experimental group was exposed to evaluative digital social interaction situations, whereas the control group engaged in neutral digital activities. Data were collected using a digital social anxiety scale and an assertiveness scale. Statistical analyses included descriptive statistics and mixed analysis of variance (mixed ANOVA). The results revealed a significant difference in assertiveness levels between the experimental and control groups following the intervention. These findings suggest that digital social anxiety has a significant impact on the assertiveness of junior high school students.